Penilaian Kondisi Jalan dengan Metode Surface Distress Indeks (SDI) pada Ruas Jalan di Kecamatan Karang Jaya Kabupaten Musi Rawas Utara - Erik Faldian; Saloma; Arie Putra Usman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increasing population movement in Musi Rawas Utara in line with the progress and growth of residential areas in the district has an impact on the high demand for the provision of adequate transportation facilities and infrastructure. In order to meet the demand for transportation facilities and infrastructure, a policy was taken to develop road infrastructure. One of the road infrastructure development policies is data on road conditions in Musi Rawas Utara Regency. Updating data on district road conditions in Karang Jaya District uses the Surface Distress Index (SDI) Method and by sorting the stable condition of road sections in Karang Jaya District, Musi Rawas Utara Regency. The results of the district road survey in Karang Jaya District in 2024 are good conditions along 5,400 km or 6.944%, moderate conditions along 21,650 km or 27.842%, lightly damaged conditions 4,300 km or 5.530% and severely damaged 46,410 km or 59.684% with road stability of 34.787% and unstable conditions of 66.213%..